Can a graft be placed over a flap in complex hypospadias surgery? An experimental study in rabbits - Mattos, Ricardo Marcondes de; Araujo, Sergio R. R. de [UNESP]; Quitzan, Juliany Gomes [UNESP]; Leslie, Bruno; Bacelar, Herick; Gomes Parizi, Joao Luiz; Caetano Martins, Gustavo Marconi; Cruz, Marcela Leal da; Macedo, Antonio (Brazilian Soc Urol, 2016)
Purpose: To develop a rabbit experimental study to test the hypothesis that surgical repair of hypospadias with severe ventral curvatures might be completed in one stage, if a graft, such as buccal mucosa, could be placed over the tunica vaginalis flap used in corporoplasty for ventral lengthening, with the addition of an onlay preputial island flap to complete the urethroplasty. Materials and methods: The experimental procedure with rabbits included a tunica vaginalis flap for reconstruction of the corpora after corporotomy, simulating a ventral lengthening operation. A buccal mucosa graft was placed directly on top of the flap, and the urethroplasty was completed with an onlay preputial island flap. Eight rabbits were divided into 4 groups, sacrificed at 2, 4, 8 and 12 weeks postoperatively, and submitted to histological evaluation. Results: We observed a large number of complications, such as fistula (75%), urinary retention (50%) and stenosis (50%). There were two deaths related to the procedure. Histological evaluation demonstrated a severe and persistent inflammatory reaction. No viable tunica vaginalis or buccal mucosa was identified. Conclusions: In this animal model, the association of a buccal mucosa graft over the tunica vaginalis flap was not successful, and resulted in complete loss of both tissues.
Keywords: Hypospadias; Urogenital Abnormalities; Urologic Surgical Procedures